Redescriptions and new host records of chewing lice of the genus Ricinus (Phthiraptera: Ricinidae) from the Neotropical Region - Valan, Miroslav; Sychra, Oldrich; Literak, Ivan (Zootaxa, 2016)
Two species of the chewing louse genus Ricinus are redescribed and illustrated: Ricinus dalgleishi Nelson, 1972 from Helmitheros vermivorum (Gmelin, 1789), a new host-louse association, and Ricinus tanagraephilus Eichler, 1956 from Euphonia laniirostris d’Orbigny & Lafresnaye, 1837. Also, new host-louse associations are recorded for Ricinus vireoensis Nelson, 1972 from Vireo pallens Salvin, 1863, and for females of an unidentified species of Ricinus sp. from Corythopis delalandi (Lesson, 1831), which are described and illustrated.